Utility of routine post-admission testing for SARS-CoV-2 in a rehabilitation facility - Victoria R. Williams; Larry Robinson; Morty Eisenberg; Kuldeep Virdi; Robert Kozak; Jerome A. Leis (Cambridge University Press, 2024)
Asymptomatic screening for SARS-CoV-2 is recommended in healthcare settings during periods of increased incidence, yet studies in rehabilitation settings are lacking. Routine weekly post-admission asymptomatic testing in a rehabilitation facility offered marginal gain beyond syndromic and targeted unit testing and was not associated with a reduced risk of healthcare-associated COVID-19.